CONCERNING CORRELATION BETWEEN METHODOLOGY AND TECHNOLOGY IN PEDAGOGICAL RESEARCH - Vladimir I. Zagvyazinsky (Образование и наука, 2015)
The purpose of the paper is the continuation of a cycle of the methodological articles, called to help work of young researchers.The general dissatisfaction with quality and results of research work in an education sphere and pedagogics has been largely caused not only insufficient level of methodological culture of competitors of scientific degrees and researchers-experts, but also their inability to choose a work technology of procedure of research that will be adequate to the purposes, problems and a plan of it. The present article is also devoted to this problem.Methods. The methods of the analysis, synthesis, idealisation, generalisation of author’s experience, a concrete definition and modelling are used.Results and scientific novelty. The general technology of scientific search in an education sphere is presented; the technology is developed on the basis of long-term experience of the Tyumen scientific and pedagogical school, and justified in practice. The author doesn’t take into consideration the rigid technology of algorithmic type which is hardly useful in works of creative character; but in the present case – frame technology that defines the expedient organisation, sequence of stages of work and its corresponding maintenance. The following technology components are described: self-determination of the researcher or research group on the basis of creation and the statement of the developed project of all procedures of search; statement of questions on initial allocation of the problem conducting ideas, a plan-way of its realisation; project performance, its ascertaining and a reformative part, research procedures (the basic stage); summarising, generalisation of the research performed, a writing of the text of report documents, preparation of total publications. Examples of typical errors of the young scientists who do not own the technology of scientific activity are given.Practical significance. Proposed recommendations stated in the paper are designated for teachers-researchers, students, master’s students, post-graduate students and doctoral students, mastering practical methodology of scientific and pedagogical search, and also to the supervisors of studies, aspiring to raise efficiency and content of the tutorial activity.